Analysis of financial inclusion in Ecuador from a multilevel approach for the year 2018 - Mantilla Varela, Roger Alejandro (2021)
Financial inclusion has gained prominence as its benefits are known in economic and social spheres. However, there is little evidence of aggregate and disaggregated factors to support it. This document explores, by means of multilevel logistics models, the individual and contextual characteristics associated with the probability of using a service point in the financial system and of having a bank account. There are many similarities at the individual level, but there are differences at the aggregate level between the determinants of access and use. The study confirms that the cantonal level does affect the level of individual financial inclusion. Different studies focus on investigating financial inclusion with aggregated and disaggregated approaches. This research combines both approaches by applying multilevel models, also known as random effects models or components of variance, through a hierarchical two-level data structure, with individuals at level 1 and cantons at level 2. The objective of this study is to determine the individual and contextual effects that influence the probability of being financially included in Ecuador. A strong point of this research is that two dependent variables are used to analyze financial inclusion.